The high incidence and bioethics of findings on magnetic resonance brain imaging of normal volunteers for neuroscience research. Issue 3 (27th February 2009) - Hoggard, N; Darwent, G; Capener, D; Wilkinson, I D; Griffiths, P D
Abstract : Background: We were finding volunteers for functional magnetic resonance imaging studies with abnormalities requiring referral surprisingly frequently. The bioethics surrounding the incidental findings are not straightforward and every imaging institution will encounter this situation in their normal volunteers. Yet the implications for the individuals involved may be profound. Should all participants have review of their imaging by an expert and who should be informed? Methods: The normal volunteers that were imaged with magnetic resonance (MR) which were reviewed by a consultant neuroradiologist. All participants completed a volunteer consent form in addition to a standard departmental MR safety screening form. The volunteer screening form requires the general practitioner details to be completed and asks the participant to consider closely the possibility and implications of finding an unexpected but potentially serious abnormality before signing. Results: 525 different individuals were scanned as normal volunteers, the mean age was 35-years and 330 were males. Of these 525, 46 had definite significant abnormalities (8.8%), mean age 50-years. Conclusion: We have found a high rate of incidental abnormalities amongst individuals participating in imaging studies at our institution. It is our current practice to inform the research study participant of the findings, counsel them and inform their primary care physician. We think that it is advisable for researchers utilising MR imaging of the brain to have access to trained neuroradiologists, a protocol in place to deal with this problem and take consent in a way that allows the participant to realise the possibility of an abnormal finding.